Assess of students’ Knowledge Concerning Effect of Lifestyle on Polycystic Ovary Syndrome - Hamid, Samahir Sabri (Jurnal Kebidanan Midwiferia, 2024)
Polycystic ovary syndrome (PCOS), also known as Stein-Leventhal syndrome, is an endocrine disorder that affects 15% to 20% of women of reproductive age and involves the presence of multiple follicular cysts on one or both ovaries. This study was conducted to assess the knowledge about PCOS, effects of lifestyle habits on PCOS and knowledge of diverse treatment methods to reduce the risks of the syndrome.180 female students from three colleges were participate a questionnaire include demographic information of students and scientific questions concerning PCOS, Among the 180 female students whose knowledge was evaluated about the effect of lifestyle on polycystic ovary syndrome, (32%) of the participants had a good knowledge rate, (53%) of them had a moderate knowledge rate, and (15%) had a poor knowledge rate.